Legal Reconstruction of Certainty of Ownership Rights for Apartment Units and Businesses in Superblock Management Through P3SRS - Lismanida (Greenation Research & Yayasan Global Resarch National, 2025)
The development of vertical housing in the form of superblocks in urban areas has changed residential ownership patterns and given rise to increasingly complex legal issues. Superblocks not only combine residential and business functions but also place unit owners in a collective legal relationship that depends on land rights, the technical age of the building, and a joint management system. This study aims to analyze the level of protection and legal certainty surrounding superblock unit ownership based on applicable positive law, while also formulating a legal reconstruction model that can address the gap between norms and practices. The results show that the Apartment Law and related regulations do not fully guarantee the sustainability of ownership rights, especially after the building has passed its technical age. The dependence of apartment unit ownership rights on Building Use Rights (Hak Guna Bangunan) or Management Rights (Hak Pengelolaan) creates structural uncertainty that directly impacts unit owners. Furthermore, weak regulations regarding the transition and authority of the Apartment Unit Owners and Occupants Association (APOS) have led to developer dominance and prolonged management conflicts. This study proposes a legal reconstruction that positions PPPSRS (Regional Unit Owners Association) as the collective rights holder of unit owners, strengthens post-building age regulations through compensation schemes, redevelopment, and priority rights, and encourages harmonization between apartment, land, and consumer protection laws. The reconstruction is expected to create legal certainty, justice, and sustainable ownership of superblock units, while also restoring public trust in the vertical housing legal system in Indonesia.